Analisis Pengaruh Kepuasan Pelanggan Terhadap Repurchase Intention Pada Aplikasi Shopee (Studi Pada Mahasiswa S1 Pengguna Aplikasi Shopee Di Universitas Sumatera Utara) - Fathur Ramadhan Siagian; Abdul Aziz Nst; Fannysia Theresa Juliarta Sijabat; Lydia Natalia Samosir; Siti Mawaddah; Onan Marakali Siregar; Afrila Mulyati Siregar (CV. ITTC INDONESIA, 2024)
his study aims to analyze the influence of customer satisfaction on repurchase intention on the Shopee application, focusing on undergraduate students at the University of North Sumatra. The research method employed is quantitative method with simple linear regression analysis as the data analysis technique. The results indicate that the t- test shows a significance value of 0.00, which is smaller than the predetermined significance level (0.05). This rejects the null hypothesis (H0) stating that there is no influence between customer satisfaction and repurchase intention. It implies that customer satisfaction has a significant influence on repurchase intention on the Shopee application.The coefficient of determination (R²) obtained is 0.695, indicating that 69.5% of the variability in repurchase intention can be explained by the level of customer satisfaction. Simple linear regression analysis also reveals that customer satisfaction has a positive and significant influence on repurchase intention. Thus, the higher the customer satisfaction with the service and shopping experience on Shopee, the higher the likelihood they will make a repurchase..